(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Fenugreek is one of the most commonly used herbal medicinal plants. Another benefit of fenugreek seeds is that it is used to enhance the flavor, color and texture of fruit. Fenugrek comprises a number of chemical components such as trigonellines, choline, flavonoids and fixed oils. SSCP –PCR is useful to reach rare and endemic species’ genetic diversity and also to resolve genetic links between populations. . PCR amplification of DNA. Genotyping of ITS4 was performed using a polymerase chain reaction technique, followed by singlestrand conformation polymorphism. Accordingly, these DNA polymorphisms were confirmed using DNA sequencing. The results appeared that the presence of three different haplotype patterns named according to the number of bands were 4-bands, 3-bands, 2 –bands using SSCP –PCR technique. The pattern of all resolved SSCP bands can however be difficult to establish using gel visualisation alone. This polymorphisms of DNA must then be verified by the use of DNA sequencing. The findings of the sequence shown that the haplotypes of the ITS region have been identified by several SNPs. Conclusion: our findings indicated that SSCP-PCR technique is more informative for evaluation of genetic diversity and relationships among fenugreek populations.